2010
DOI: 10.1002/lt.22064
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of early de novo cancer in liver graft recipients treated with cyclosporine: An association with C2 monitoring and recipient age

Abstract: The goal of this study was to determine the risk factors for de novo cancer after liver transplantation (LTx). Retrospective analyses were performed in 385 LTx patients who underwent transplantation between 1986 and 2007. In total, 50 (13.0%) recipients developed de novo malignancy. The cumulative incidence of de novo cancer at 1, 5, 10, and 15 years after LTx was 2.9% 6 0.9%, 10.5% 6 1.8%, 19.4% 6 3.0%, and 33.6% 6 6.8%, respectively. The standardized incidence ratio of malignancy in LTx patients compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 49 publications
3
43
2
Order By: Relevance
“…Although immunosuppressive therapy after LT is associated with a standardized incidence ratio of malignancy of 2.2 as compared with the general population, 31 we demonstrated that immunosuppression does not correspond to increased development of features associated with malignant transformation of IPMN. Specifically, cyclosporine therapy and duration of an immunosuppressed state have been shown to be independent determinants of cancer development in post-LT patients.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Although immunosuppressive therapy after LT is associated with a standardized incidence ratio of malignancy of 2.2 as compared with the general population, 31 we demonstrated that immunosuppression does not correspond to increased development of features associated with malignant transformation of IPMN. Specifically, cyclosporine therapy and duration of an immunosuppressed state have been shown to be independent determinants of cancer development in post-LT patients.…”
Section: Discussioncontrasting
confidence: 48%
“…Specifically, cyclosporine therapy and duration of an immunosuppressed state have been shown to be independent determinants of cancer development in post-LT patients. 31 Tacrolimus has been reported to be superior to cyclosporine in reducing mortality, graft loss, and acute rejection and improving renal function, lipid profiles, and blood pressure. 32,33 As our study did not demonstrate a preference for either calcineurin inhibitor, it does not appear that the choice of immunosuppression should be based on the presence of 34 Because of our limited sample size of patients on multiple immunosuppressants, we could not evaluate the effects of this regimen compared with single-agent therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one single-centre study has described an increased risk of malignancy in liver transplant patients treated with cyclosporine compared with tacrolimus [28]. However, the authors admit that a different monitoring was used for cyclosporine, and lower rejection rates were detected in this group, suggesting higher immunosuppressive potency with cyclosporine than with tacrolimus in this series.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 70%
“…240 Challenges still remain, however, in determining the type and dose of immunosuppressive therapy posttransplant to further reduce HCC recurrence and improve its prognosis. CNIs in general are reported as having direct prooncogenic activity 241 ; high levels of cyclosporine (>300 ng/mL) and tacrolimus (>10 ng/mL) have been associated with an increased risk of HCC recurrence. 242 mTORi have antiangiogenic and antiproliferative properties.…”
Section: Overimmunosuppression and Cancermentioning
confidence: 99%